Prospective trial of oestrogen and calcium in postmenopausal women. Issue 6090 (24th September 1977) - Horsman, A; Gallagher, J C; Simpson, M; Nordin, B E
Abstract : In a prospective trial in 72 postmenopausal women to compare the effects on bone loss of no treatment, treatment with oestrogen, and treatment with calcium the women were followed up for at least two years and examined densitometrically and morphometrically. Women in the untreated control group continued to lose bone during the two years, whereas the oestrogen-treated group lost none. Loss in the calcium-treated group was intermediate. Oestrogen appeared to inhibit endosteal bone resorption and may have stimulated subperiosteal bone apposition.